Enfoques latinoamericanos en el estudio de los movimientos sociales (2022)
The study of social movements in Latin America has gained great relevance since the 1980s. This interest in collective action coincides with the emergence of Latin American approaches to its study, which have emphasized the relationship between a central conflict in society and how it impacts collective action. This paper discusses four of these approaches: popular movements, democratization, anti-neoliberal and indigenous mobilization. Likewise, it presents how these approaches are the basis for a Latin American theory of social movements that are being developed.